Molecular insights into the functional role of PbNRT2.4 in potassium homeostasis and nutrient transport in Pyrus ussuriensis - Han Yang; Hao Xu; Yujie Shi; Liyan Chen; Lijuan Zhang; Liping Kan; Yumeng Jin; Xinlan Mei; Yangchun Xu; Nazir Ahmed; Caixia Dong (Plant Stress)
Potassium (K), often referred to as the ‘quality element’, is essential for nutrient absorption in fruit trees, with the efficiency of the rootstock's nutrient utilization being a critical factor in the plant's overall nutrient status. Pyrus ussuriensis, identified as a variety with high potassium efficiency, demonstrates superior tolerance to potassium-deficient conditions and a significant affinity for potassium, compared to Pyrus betulifolia, attributed to its proficient capacity for potassium ion redistribution. This study delves into the molecular mechanisms underlying this high potassium efficiency, focusing on PbNRT2.4 gene, a pivotal regulatory factor in the absorption and translocation of potassium. Predominantly expressed in the roots, PbNRT2.4, is finely regulated by potassium concentrations, as well as exogenous sugar levels. Under K+ limitation, sucrose and sorbitol application significantly upregulates PbNRT2.4 expression in P. ussuriensis, thereby enhancing K+ absorption. In yeast systems, PbNRT2.4 facilitates K+ uptake, and its overexpression in hairy root systems, particularly in P. ussuriensis, leads to a marked increase in K+ influx in the root and xylem. Overexpression of this gene in pear callus tissues similarly increased intracellular K+ levels under K-deficient conditions. Interactions among PbNRT2.4, PbHAK11, and PbSDH1 proteins, elucidated using yeast two-hybrid, BiFC, and Co-IP assays, are crucial for modulating carbon and nitrogen metabolic processes, thereby harmonizing K+ absorption and transport. These findings provide a detailed understanding of potassium homeostasis at a molecular level.